2022
DOI: 10.1186/s12889-022-12732-w
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook to promote the uptake of colorectal cancer screening

Abstract: Background The use of social media presents a unique opportunity for cancer screening programs to motivate individuals to get screened. However, we need a better understanding of what types of social media messages for colorectal cancer (CRC) screening are preferred. The objective of this study was to develop social media messages promoting CRC screening uptake to identify messages preferred by the target audience. Methods We conducted a qualitativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…These authors found that HPV awareness could be increased through brief participation in this social media platform and the receipt of tailored health messages [ 11 ]. Similar studies have been reported for liver cancer [ 12 ] and colorectal cancer [ 13 ]. Although the use of mHealth in cancer management is currently limited to examinations, test reminders and health education, new applications including intervention measures are worth investigating.…”
Section: Introductionsupporting
confidence: 87%
“…These authors found that HPV awareness could be increased through brief participation in this social media platform and the receipt of tailored health messages [ 11 ]. Similar studies have been reported for liver cancer [ 12 ] and colorectal cancer [ 13 ]. Although the use of mHealth in cancer management is currently limited to examinations, test reminders and health education, new applications including intervention measures are worth investigating.…”
Section: Introductionsupporting
confidence: 87%
“…Nowadays, with the advancement of communication technology, people prefer to read from their mobile phone using mobile applications or web browsers rather than the traditional printed material. Previous studies have demonstrated that mobile phone-based health education could improve residents' knowledge of CRC prevention [37][38][39]. In addition, mobile phone-based text message reminders could also increase the participation rate of CRC screening among the target population [40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Further examples include the [ 24 , 25 ], which supply Facebook ® and Twitter ® with resources to encourage the practice of so-called correct COVID-19 behaviour and other relevant COVID-19 information. There is also an increasing use of social media, e.g., Facebook ® and LinkedIn ® in hospitals as institutions, mainly for public relations, health education, and health-promoting/preventive tasks [ 26 , 27 , 28 , 29 , 30 , 31 ]. Studies also show that social media use amongst nurses, but also students and faculty members, awakens both curiosity and caution, speaking for the need of education and policy to support the use of social media as a professional tool [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%